Grammar and philosophy in late antiquity : a study of Priscian's sources - Luhtala, Anneli (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences, 2005)
This book examines the various philosophical influences contained in the ancient description of the noun. According to the traditional view, grammar adopted its philosophical categories in the second century B.C. and continued to make use of precisely the same concepts for over six hundred years, that is, until the time of Priscian (ca. 500). The standard view is questioned in this study, which investigates in detail the philosophy contained in Priscian's Institutiones grammaticae. This investigation reveals a distinctly Platonic element in Priscian's grammar, which has not been recognised in.